HIV Stigma Reduction for Health Facility Staff: Development of a Blended- Learning Intervention - Laura Nyblade; Krishnamachari Srinivasan; Amanda Mazur; Tony Raj; Divya S. Patil; Dhinagaran Devadass; Kedar Radhakrishna; Maria L. Ekstrand; Maria L. Ekstrand (Frontiers Media S.A., 2018)
Introduction: The effect of stigma on health and health inequity is increasingly recognized. While many medical conditions trigger stigmatization, the negative effects of HIV stigma are particularly well documented. HIV stigma undermines access, uptake, and adherence to both HIV prevention and treatment. People living with HIV face stigma in all aspects of their daily lives; however, stigma in the health system is particularly detrimental. A key component for health facility stigma-reduction interventions is participatory training of staff, often through several days of in-person training. Though this approach shows promise, it is time intensive and poses challenges for busy health facilities. In response, the DriSti study has developed a brief blended-learning approach to stigma reduction in Karnataka State, India. This paper describes the process and final content of the intervention development. The intervention is currently being tested. Final evaluation results will be published upon study completion.Methods: Grounded in behavior change strategies based on social cognitive theory principles that stress the importance of combining interpersonal interactions with specific strategies that promote behavior change, we used a three-phase approach to intervention development: (1) content planning-review of existing participatory stigma-reduction training activities; (2) story boarding-script development and tablet content production; and (3) pilot testing of tablet and in-person session materials.Results: The final intervention curriculum consists of three sessions. Two initial self-administered tablet sessions focus on stigma awareness, attitudes, fears of HIV transmission, and use of standard precautions. The third small group session covers the same material but includes skill building through role-play and testimony by a person living with HIV. A study team member administers the tablet sessions, explains the process, and is present throughout to answer questions.Conclusion: This paper describes the theoretical underpinning and process of developing the blended-learning curriculum content, and practical lessons learned.The approach covers three key drivers of HIV stigma-stigma awareness, fear of HIV transmission, and attitudes. Developing video content for the self-directed learning is complex, requires a diverse set of people and skills, and presents unexpected opportunities for stigma reduction. Co-facilitation of the in-person session by someone living with HIV is a critical component.